Global burden, trends, and projections to 2050 of neuroblastoma and other peripheral nervous cell tumors: a systematic analysis of the global burden of disease study from 1990 to 2021 - Wu, Hang; Li, Jingjing; Yang, Yue; Xuan, Xiaoqi; Yang, Jinlong (Frontiers in Pediatrics, 2025)
BackgroundNeuroblastoma and other Peripheral Nervous Cell Tumors (NPNTs) contribute substantially to global pediatric cancer morbidity and mortality, particularly among children under five. This study provides a comprehensive analysis of the global burden of NPNTs, examining long-term trends from 1990 to 2021 and projecting future patterns through 2050, based on data from the Global Burden of Disease (GBD) Study 2021.MethodsWe analyzed mortality and disability-adjusted life years (DALYs) from 1990 to 2021 using GBD data. Trends were assessed via age-standardized rates (ASRs) and estimated annual percentage change (EAPC). Predictive models (Exponential Smoothing and ARIMA) projected future burden through 2050. Analyses were stratified by age, sex, and socio-demographic index (SDI) regions.ResultsIn 2021, NPNTs resulted in 5,194 deaths (95% UI: 4,295–5,932) and 285,479 DALYs (95% UI: 227,709–341,110) globally. Children under five years accounted for 1,355 deaths (26.1% of total) and 126,215 DALYs (44.2% of total), with males exhibiting higher mortality rates (ASR: 0.08 vs. 0.06 per 100,000 in females). Middle-SDI regions experienced the highest number of deaths (1,503) and DALYs (79,412), while high-SDI regions had the highest age-standardized death rate (0.09 per 100,000) and DALYs rate (5.25 per 100,000). From 1990 to 2021, population growth drove 90.2% of DALYs increases, while aging offset 13.0% of the rise. Projections diverged: ES models predicted stable trends, whereas ARIMA forecasted a 22.3% increase in male DALYs by 2050 (from 165,574 to 226,533).ConclusionsThe escalating burden of NPNTs is strongly tied to demographic expansion and inequitable healthcare access. Prioritizing early diagnosis in high-burden regions (e.g., middle/low-SDI settings) and addressing sex-specific disparities are imperative. These findings call for data-driven policies to mitigate future disease burden through targeted resource allocation and surveillance strengthening.